Research on Hydraulic Fracturing Technology for Roof Stratigraphic Horizon in Coal Pillar Gob-Side Roadway - Sun, Tong; Li, Zhu; He, Qingyuan; Ma, Dan; Liu, Benben; Gao, Xuefeng (Applied sciences, 2025)
The return roadway in Limin Coal Mine experiences strong mine pressure during the mining work of the I030902 working face, which poses potential safety hazards to production and management. Therefore, hydraulic fracturing is used to relieve pressure on the free coal pillar roof. Hydraulic fracture simulation tests using gelatin materials were conducted, and the propagation of the hydraulic fracturing cracks in gelatin simulating different key strata was obtained, which led to the design of the hydraulic fracturing used in the I030902 working face at Limin Coal Mine. According to the analysis of the on-site tests, after fracturing, the roof pressure decreased by 17.8%, the average pressure step distance reduced by 18.0%, the average daily rate of the roof and floor convergence decreased by 63.86%, and the average daily rate of the roof and floor convergence was reduced by 72.4%. Therefore, the feasibility of the hydraulic fracturing in weak structure formation in hard roof strata and roadway deformation control has been verified, providing a theoretical foundation and on-site date for the relief of free roadway roof pressure.